Pengaruh Media Sosial terhadap Proses Pengambilan Keputusan Pembelian Pelanggan pada Usaha Kecil Sajodo Snack Bandung, Indonesia - Amini, Dini Nasya (Asosiasi Ahli Administrasi Indonesia, 2023)
The study aims to determine and analyze the effect of social media on the process of purchase decision making by customers purchase decision making in Small Enterprise Sajodo Snack. The quantitative descriptive research method, while the data used primary data collected through questionnaires to 110 respondents and analyzed using descriptive, correlation and regression. The research showed The results showed that the use of social media has a significant effect on the process of customer purchasing decisions in Small Enterprise Sajodo Snack significantly with Sig. 0.000. And the results show that the use of social media has a positive and strong effect on the purchasing decision-making process of 55,8%.